2011
DOI: 10.1002/cbf.1738
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of the safe margin, antithrombotic and antiproliferative actions for the treatment of restenosis: Nitric oxide donor and polymers

Abstract: Drug-eluting stents (DES) were developed to combat the problem of in-stent restenosis, and evaluating the biological activity from DES systems is critical for its safety and efficacy. To test the cytotoxicity of nitric oxide (NO) donor-containing polymers for their potential use in DES applications, S-nitrosoglutathione (GSNO) or in combination with poly(vinyl alcohol) (PVA) and poly(vinyl pyrrolidone) (PVP) in an aqueous polymeric solution (PVA/PVP/GSNO) was investigated using Balb/c 3T3 and Rabbit arterial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Accordingly, fibrin agglomerates seemingly play a beneficial role in clearing fibrin fragments during fibrinolysis, or a potentially deleterious role if generated under coagulation conditions and not removed from the circulation. This may be of significance in the design of drug-eluting stents to prevent restenosis, where GSNO is combined with a polymeric coating, and has the property of inhibiting platelet aggregation with an EC50 of 5.0 mM [28]. Our results suggest this concentration of GSNO could induce local formation of fibrin agglomerates that may enter the circulation and potentially plug the downstream microcirculation.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Accordingly, fibrin agglomerates seemingly play a beneficial role in clearing fibrin fragments during fibrinolysis, or a potentially deleterious role if generated under coagulation conditions and not removed from the circulation. This may be of significance in the design of drug-eluting stents to prevent restenosis, where GSNO is combined with a polymeric coating, and has the property of inhibiting platelet aggregation with an EC50 of 5.0 mM [28]. Our results suggest this concentration of GSNO could induce local formation of fibrin agglomerates that may enter the circulation and potentially plug the downstream microcirculation.…”
Section: Discussionmentioning
confidence: 72%
“…Additionally, GSNO modulates hemostasis by inhibiting platelet activation and aggregation, and decreasing fibrinogen binding to platelets [22]–[25]. GSNO has been used clinically as an antithrombotic agent [26], [27] and is also being incorporated into drug-eluting stents to prevent restenosis [28].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Sorragi et al carried out cytotoxicity studies using GSNO donors combined with poly(vinyl alcohol) (PVA) and poly(vinyl pyrrolidone) (PVP) in aqueous solution (PVA/PVP/GSNO) for coating DES 64. Cell growth studies found that both GSNO and PVA/PVP/GSNO induced anti‐proliferative effects in rabbit SMCs and inhibited platelet aggregation.…”
Section: No‐generating Materialsmentioning
confidence: 99%
“…For example, poly(vinyl alcohol) and poly(vinyl pyrrolidone) polymer solutions reduced the cytotoxicity and enhanced the anti-proliferative effects of GSNO in smooth muscle cell cultures. [56] In this section, recent research on the development of polymer-based NO-releasing and -generating materials without evaluation in vivo are discussed (2006–2011) (Scheme 1). Previous research work on this topic has been reviewed elsewhere.…”
Section: Novel No-releasing and No-generating Polymeric Materialsmentioning
confidence: 99%